2020
DOI: 10.1007/s13762-020-02684-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of transient sea level rise impacts on water quality of unconfined shallow coastal aquifers

Abstract: This study analyzes the impacts of 1 m gradual and instantaneous sea level rise combined with pumping activity on seawater wedge toe location in a shallow coastal aquifer located in the southern shores of the Caspian Sea. The gradual sea level rise scenario investigates the transition variation of seawater wedge toe due to linear and parabolic between the years 2015 and 2100. Moreover, the maximum value of saltwater intrusion due to variations in hydraulic conductivity and aquifer's recharge rates is analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…There has been an unprecedented rise in global sea levels, with devastating physical and socioeconomical effects on the coastal communities (Nicholls and Cazenave 2010;Nidhinarangkoon et al 2020;Ranjbar et al 2020;Schaefer et al 2020;Shi et al 2020;Stammer et al 2013). Since the start of the 20th century, the Global Mean Sea Level (GMSL) has risen by about 16-21cm, with more than 7 cm of this occurring since 1993 (Global Change Research Program 2019;Jevrejeva et al 2016;Yi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been an unprecedented rise in global sea levels, with devastating physical and socioeconomical effects on the coastal communities (Nicholls and Cazenave 2010;Nidhinarangkoon et al 2020;Ranjbar et al 2020;Schaefer et al 2020;Shi et al 2020;Stammer et al 2013). Since the start of the 20th century, the Global Mean Sea Level (GMSL) has risen by about 16-21cm, with more than 7 cm of this occurring since 1993 (Global Change Research Program 2019;Jevrejeva et al 2016;Yi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Shoreline changes, rising frequency and intensity of flooding, erosion, change in coastal aquifers quality and groundwater are some of the physical impacts of SLR on coastal communities (A. Cazenave and Llovel 2010;Church and White 2011;Nicholls and Cazenave 2010;Ranjbar et al 2020;Werner and Simmons 2009). The socio-economic consequences of SLR include water and soil quality degradation, loss of lives, properties, damage to infrastructures, and depletion of agricultural resources (Ghazali et al 2018;IPCC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The major supplier of freshwater globally is groundwater and freshwater globally is of limited amount. Unfortunately, this very little amount of freshwater becomes subjected to salt/seawater intrusion (Loáiciga et al 2012;Werner et al 2013;Sharip et al 2019;Ranjbar et al 2020). Sea level rise and tidal fluctuations induced by global warming will result in increased saltwater intrusion into freshwater bodies, invariably affecting groundwater quality (Li et al 2001;Pool et al 2014;Sefelnasr and Sherif 2014;Kuchaksaraei et al 2019;Ranjbar et al 2020).…”
Section: Salt/sea Water Intrusionmentioning
confidence: 99%
“…Unfortunately, this very little amount of freshwater becomes subjected to salt/seawater intrusion (Loáiciga et al 2012;Werner et al 2013;Sharip et al 2019;Ranjbar et al 2020). Sea level rise and tidal fluctuations induced by global warming will result in increased saltwater intrusion into freshwater bodies, invariably affecting groundwater quality (Li et al 2001;Pool et al 2014;Sefelnasr and Sherif 2014;Kuchaksaraei et al 2019;Ranjbar et al 2020). Recently, some studies have shown that the predicted sea-level rise by the year 2100 will be between 0.2m and 0.8m, which will cause extensive flooding of coastal regions (Vermeer and Rahmstorf 2009;IPCC 2013Ranjbar et al 2020.…”
Section: Salt/sea Water Intrusionmentioning
confidence: 99%
“…Abd-Elhamid et al [30] examined the individual and combined effects of predicted SLR and over-pumping on SWI using a coupled transient density-dependent finite element model to simulate SWI in the Gaza aquifer. Ranjbar [31] analyzed the effects of a 1 m gradual and immediate SLR associated with pumping activities on the location of seawater wedge toe in a shallow coastal aquifer on the Caspian Sea's southern shores. Essink and Schaars [32] developed a model to simulate GW flow, heat and salinity distribution, and seepage and salt load flux into the surface water system.…”
Section: Introductionmentioning
confidence: 99%